Kinetics of Phenol Degradation in Aqueous Solution Oxidized under Low Frequency Ultrasonic Irradiation - Marwan Marwan (Jurnal Rekayasa Kimia & Lingkungan, 2014)
Phenol is categorized as a refractory pollutant and its presence in water stream is strictly limited according to the government regulation. The present study investigated the degra-dation of phenol in aqueous solution by the effect of ultrasound. The process took place in a 500 ml glass reactor equipped with magnetic stirring and irradiated by low frequency (28 kHz) ultrasound from a horn type probe. Ultrasonic irradiation was found to enhance oxidation rates at ambient conditions, compared to other approaches. Optimum conditions were observed at a stirring speed of 400 rpm and temperature of 30 C in acidic solution. It was revealed that the phenol degradation was the first order kinetics with respect to phenol. A low value of the activation energy 6.04 kcal/mol suggested that diffusional steps were rate determining during the phenol decomposition. It also confirmed that phenol was mostly degraded in the film region and less occurred in the bulk solution.